Getting to the Heart of the Matter: The Role of Regulatory T-Cells (Tregs) in Cardiovascular Disease (CVD) and Atherosclerosis - Albany, Caraugh J.; Trevelin, Silvia C.; Giganti, Giulio; Lombardi, Giovanna; Scottà, Cristiano (Frontiers in Immunology, 2019)
Cardiovascular diseases (CVD) are the leading cause of mortality worldwide. Although their increasing incidence and significant expenses compromising the healthcare system in both western and developing countries, no curative therapy currently exists for most of these conditions. Atherosclerosis is directly associated with CVD and is characterised by slow progressing inflammation which results in the deposition and accumulation of lipids beneath the endothelial layer in conductance and resistance arteries. Both chronic inflammation and disease progression have been associated with several risk factors, including but not limited to smoking, obesity, diabetes, genetic predisposition, hyperlipidaemia and hypertension. Currently, atherosclerotic patients rely on surgical intervention to avoid or revert vessel occlusion, and pharmacological management of the aforementioned risk factors. However, neither of these approaches completely resolve the underlying inflammatory environment which perpetuates the disease. As such, immunomodulation could provide novel therapeutic options for atherosclerosis; shifting the balance from proatherogenic to athero-protective. Indeed, regulatory T-cells (Tregs), which constitute 5-10% of all CD4+ T lymphocytes in the peripheral blood, have been shown to be athero-protective and could work as new targets in CVD and atherosclerosis. This review aims to give a comprehensive overview about the roles of Tregs in CVD focusing on atherosclerosis.